Priapism as the initial symptom of primary penile lymphoma: A case report - GONG, ZHAOHUA (D.A. Spandidos, 2014)
Primary penile lymphoma presenting with priapism as the initial symptom is extremely rare. In total, <10 cases have been previously reported. The diagnosis can be difficult and patients often develop metastasis. The current study reports the case of a 48-year-old male, who presented with a one-month history of painless priapism. On admission to Yantai Yuhuangding Hospital Affiliated to Qingdao University (Yantai, China), examination revealed an erect penis, enlarged lymph nodes in the bilateral inguinal and swelling in the thighs. A biopsy was taken from the right inguinal lymph node and the pathological diagnosis confirmed a diffuse large B-cell type of non-Hodgkin’s lymphoma, while an enhanced computed tomography scan of the chest revealed evidence of the invasion of malignant lymphoma cells. Priapism disappeared two days following the completion of the first cycle of chemotherapy with the E-CHOP regimen (cyclophosphamide, vincristine, prednisone, epirubicin and etoposide); however, evidence of brain metastases was observed one month later, which was confirmed by magnetic resonance imaging. The patient received cranial radiotheraphy and systemic treatment for cerebral edema. The patient did not respond well to treatment and succumbed to the disease three months following the initial diagnosis of lymphoma. Lymphoma may be difficult to diagnose, depending on the initial symptoms; therefore, the patient history must be carefully assessed so as to determine an early diagnosis and prevent metastasis, thus improving the prognostic outcome.